An Outline of the Issue of Justice and Equity in Canon Law - Przytulski, Mateusz (Prawo Kanoniczne, 2026)
The problem addressed: Canon law, as the normative order of the Church, is grounded not only in the need to ensure order and legal certainty, but also in a theological understanding of the human person and their supernatural vocation. In this context, the categories of justice and equity are of key importance, being present both in the philosophical and Roman tradition as well as in biblical and theological reflection. Contemporary practice in the application of ecclesiastical law reveals a tension between the general character of legal norms and the concreteness of individual human situations, which justifies a deeper analysis of the relationship between justice and equity, especially in light of the principle salus animarum. The aim of the research conducted: The aim of the article is to present the place and significance of justice and equity in canon law and to determine the relationship between these concepts from the perspective of the canonical tradition and the binding legislation of the Church. Methods: The study employs dogmatic-legal, historical-legal, and canonistic methods. It includes a synthetic analysis of philosophical sources, Roman legal maxims, biblical texts, Thomistic doctrine, and the provisions of the 1983 Code of Canon Law, taking into account selected elements of Rotal jurisprudence and papal teaching. The results of the research: The study demonstrates that justice constitutes the foundation of the Church’s legal order, guaranteeing the protection of the rights of the faithful and the objectivity of norms. Equity – both natural and canonical – does not negate justice but complements it, enabling a personalistic and pastoral application of the law. The conclusions drawn from the research: Justice and equity remain in a complementary relationship: the former ensures stability and legal certainty, while the latter allows the application of the law to be adapted to concrete circumstances without undermining its essence. Natural equity refers to human dignity and natural law, whereas canonical equity is an institution proper to canon law that makes it possible to overcome the tension between the letter and the spirit of the law. The ultimate interpretative criterion remains the principle salus animarum suprema lex, which presents ecclesiastical law as an instrument serving the good and salvation of the human person.